The Relationship Between Smoking Behavior and Mental Health (Mental Distress) In Generation Z Students - Santi Esterlita Purnamasari; M. Deny Adiantoro (Annpublisher, 2026)
Aims. This study aims to determine the relationship between smoking behavior and mental health in Generation Z students. Methods. This research involved 104 Generation Z students who are active smokers in Indonesia using a purposive sampling technique. The instruments used were the Glover-Nilsson Smoking Behavior Questionnaire to assess smoking behavior and the Self-Reporting Questionnaire to assess mental health. Data analysis used the Pearson Product-Moment correlation technique. Result. The results showed a significant positive correlation between smoking behavior and mental health, with a correlation coefficient of 0.232 and a significance value of 0.018. This finding indicates that the higher the smoking behavior of Generation Z students, the higher the mental distress experienced. Conclusion. The contribution of smoking behavior to mental distress was 5.4 percent, while the remaining 94.6 percent was influenced by other factors not examined in this study. Implementation. This research is expected to provide empirical evidence for developing comprehensive prevention and intervention programs related to smoking behavior and mental health in universities.